When changes went into effect: Hungarians from Transylvania permitted to cross the Western border from 1985 (Academic Journal of Internal Affairs, 2020)
In the final years of socialism, Hungarians in Transylvania were going through the fires of adversity. Their circumstances were also enhanced by the significant tension at the time between the Romanian and Hungarian parties and government authorities. The circumstances of the Hungarians living in Romania were to be relieved by the strictly confidential action that permitted those being in Hungary legally to secretly travel on to Austria or Yugoslavia.
Keywords: border check; border force; traffic checkpoint; passport controller